2020
DOI: 10.3390/rs12081251
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Earth Observation Techniques in Monitoring High Mountain Environments at the Example of Pasterze Glacier, Austria: Data, Methods, Accuracies, Processes, and Scales

Abstract: Earth observation offers a variety of techniques for monitoring and characterizing geomorphic processes in high mountain environments. Terrestrial laserscanning and unmanned aerial vehicles provide very high resolution data with high accuracy. Automatic cameras have become a valuable source of information—mostly in a qualitative manner—in recent years. The availability of satellite data with very high revisiting time has gained momentum through the European Space Agency’s Sentinel missions, offering new applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 144 publications
(187 reference statements)
0
15
0
Order By: Relevance
“…Owing to frequent geo-hazards, regional development delays, poor road conditions, and low access to glaciers and glacial lakes, field investigations are difficult to conduct in the HMA. However, with the recent rapid development of remote sensing technology and cloud-based geospatial data distribution, efficient and reliable mapping methods have been widely used in cryosphere science [31,32]. To better assess and mitigate the risks of GLOFs hazard and their impact, it is crucial to investigate the evolution of the glaciers and glacial lakes and predict their future development trends under climate change [33].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to frequent geo-hazards, regional development delays, poor road conditions, and low access to glaciers and glacial lakes, field investigations are difficult to conduct in the HMA. However, with the recent rapid development of remote sensing technology and cloud-based geospatial data distribution, efficient and reliable mapping methods have been widely used in cryosphere science [31,32]. To better assess and mitigate the risks of GLOFs hazard and their impact, it is crucial to investigate the evolution of the glaciers and glacial lakes and predict their future development trends under climate change [33].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the warming of the ice at the base of hanging glaciers, possibly leading to destabilisation, has been studied at the Mont Blanc massif (Deline et al 2012;Gilbert et al 2015). The present and future formations of proglacial lakes have been studied, particularly around the Pasterze glacier (Avian et al 2020), Rhône glacier (Church et al 2018) and Mer de Glace (Magnin et al 2020).…”
Section: Processes Studied In Glacier Tourism Areasmentioning
confidence: 99%
“…Two processes associated with the present paraglacial period have also been studied at every site. The first one is glacial debuttressing (Deline et al 2012), which leads to landslides, as observed in the left lateral moraine of the Aletsch glacier in 2015, resulting in a volume of about 50,000 m 3 (Kos et al 2016), and around the proglacial lake of the Pasterze glacier (Avian et al 2020). The consequences of debuttressing on the access to huts have also been studied, for example, in the Mer de Glace basin (Mourey and Ravanel 2017).…”
Section: Processes Studied In Glacier Tourism Areasmentioning
confidence: 99%
“…In 1959-2019, Pasterze Glacier receded by 1550 m, 3 times the mean value for all Austrian glaciers (520 m), related to its large size. Today, Pasterze Glacier is characterized by annual mean recession rates in the order of magnitude of 40 m yr −1 (Lieb and Kellerer-Pirklbauer, 2018) causing a rather high pace of glacial to proglacial landscape modification favouring paraglacial response processes (Ballantyne, 2002;Avian et al, 2018). Location of the study area within Austria.…”
Section: Study Areamentioning
confidence: 99%